2014
DOI: 10.1111/hel.12153
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori Infection and its Relation with Body Mass Index in a Chinese Population

Abstract: Our results showed that BMI was significantly and positively associated with H. pylori infection, and a high BMI was associated with an increased risk of the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 43 publications
(56 reference statements)
4
56
2
2
Order By: Relevance
“…However, there is little data to support that hypothesis other than conflicting data from comparisons of obesity rates among those with and without H pylori infection 98, 99 . Obesity is a manifestation of an imbalance between energy intake and expenditure, so the absence of H pylori might increase appetite and intake.…”
Section: Obesitymentioning
confidence: 99%
“…However, there is little data to support that hypothesis other than conflicting data from comparisons of obesity rates among those with and without H pylori infection 98, 99 . Obesity is a manifestation of an imbalance between energy intake and expenditure, so the absence of H pylori might increase appetite and intake.…”
Section: Obesitymentioning
confidence: 99%
“…El análisis inicial de nuestro estudio mostró una mayor prevalencia de sobrepeso, obesidad, hipertensión arterial, diabetes mellitus y síndrome metabólico en los pacientes con dispepsia infectados por la bacteria. Algunos estudios han encontrado que esta bacteria desempeña un papel importante en los trastornos cardiometabólicos y recientemente su presencia se ha asociado en forma significativa y consistente con mayor índice de masa corporal, sobrepeso y obesidad en la población China 22,23 . Sin embargo, esta relación no es clara pues otros estudios han demostrado una relación inversa entre la infección por la bacteria y la prevalencia de sobrepeso y obesidad tanto en niños como en adultos de países desarrollados 24,25 .…”
Section: Discussionunclassified
“…In Korea, a large-scale study showed that the prevalence of H. pylori infection was 54.4% and that it decreased from 66.9% (1998) to 59.6% (2005) and 54.4% (2013) [6] . In China, the prevalence of H. pylori infection was reported as 43.8-47.0% [7,8] . Moreover, similar to Japan and Korea, Chen et al [8] showed that the prevalence of H. pylori infection is decreasing in China.…”
Section: The Geographic Significance Of H Pylori Infection Chronic mentioning
confidence: 99%